Histochemical alterations in lantana toxicity* - MANDIAL, R K; RANDHAWA, S N S; ROY, K S (The Indian Journal of Animal Sciences, 2014)
Cryostat section of liver, kidneys, rumen, jejunum, spleen, heart, cerebrum, lungs and gall bladder of buffalo calves (Bubalus bubalis) experi mentally intoxicated by oral administration of dried leaf powder of Lantana camara variety aculeata red flower @ 6 g/kg body weight were studied for histochemieal/histoenzymatic changes. Most of the tissues revealed loss of alkaline phosphatase, succinic dehydrogenase, lactic dehydrogenase, adenosine triphosphatase, cytochrome oxidase and xanthine oxidase activity associated with increased acid phosphatase activity and lipid contents.